Estructura productiva y desigualdad salarial: Evidencia para América Latina - Matías Ciaschi; Luciana Galeano; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2019)
– This paper studies the evolution of skill premia and its relationship with the productive structure for sixteen countries in Latin America, using microdata from household surveys and information from National Accounts for the period 1991-2015. The evidence suggests that the change in the productive structure is significantly correlated to the dynamics of wage inequality. In particular, when the share in total value added of sectors that are more intensive in high-skilled labor grows, the skill premium increases significantly.
Keywords: D31; I26; J21; J31; 330